Azzu Bahulu Ledang / Muhammad Ruzaini Sazali, Muhammad Saifuddin, Muhammad Fakhrul Hilmi Abd Ghani, Muhammad Faris Norizan, Muhammad Faiz Mat Zan and Muhammad Nur Hamizan Mohd Suhaimy - Sazali, Muhammad Ruzaini; Saifuddin, Muhammad; Abd Ghani, Muhammad Fakhrul Hilmi; Norizan, Muhammad Faris; Mat Zan, Muhammad Faiz; Mohd Suhaimy, Muhammad Nur Hamizan (2019)
Known as ‘kuih bahulu’ in the Malay language, these Asian madeleine are famous in Malaysia, Brunei and Singapore. These dainty fluffy cakes are slightly crusty on the outer layer but soft on the inside. Kuih bahulu is a traditional cake or snack usually baked in brass moulds which usually come in all sorts of sizes and shapes like fishes, flowers and most commonly, sea shells as those shown in this video above. As the main ingredient is egg, kuih bahulu is sometimes known as egg sponge cake. Compared to many western cakes, it is much lighter, less dense and has a subtle sweetness. That makes it much healthier than the usual cakes.